Genomic Profiling Reveals Synchronous Bilateral Lung Adenocarcinomas With Distinct Driver Alterations of EML4-ALK or TPM3-ROS1 Fusion: A Case Report - Tan, Benxu; Jiang, Xuan; Wang, Ruping; Tang, Cuiping; Liu, Sisi; Wu, Xue; Xia, Lei; Yu, Xian; Yang, Zhenzhou (Frontiers in Oncology, 2019)
Background: ALK and ROS1 rearrangement accounts for 3-6% and 1-3% of non-small cell lung cancers, respectively, while coexistence of them is extremely rare. Only three cases were ever reported with concurrent of ALK/ROS1 fusions in the single tumor. Comprehensive genetic profiling via next-generation sequencing (NGS) can provide fully molecular diagnosis. Case Presentation: A 50-year old Chinese female with resectable stage IB bilateral lung adenocarcinomas (ADCs) harbored EML4 exon 6-ALK exon 19 and TPM3 exon 8-ROS1 exon 35 fusions in the right lower and the left upper tumors, respectively. The results confirmed at both DNA and RNA level using NGS. Further genetic association analysis reveals that these tumors are synchronous multiple primary lung cancers with no shared gene alterations or arm-level copy number variations (CNVs). No recurrence was observed during 12 months of post-surgery follow-up. Conclusions: Our case is the first report of concurrent ALK/ROS1 fusions as distinct driver events of multiple primary lung cancers, and suggest that individual genetic testing for each of the multiple primary tumors may be necessary for fully molecular diagnosis and future treatment decision-making.